Eruption cyst in a 2 y.o. patient located in the region of upper first deciduous molar - Osica, Piotr; Osica, Karolina; Hejduk, Cezary; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
The article presents a case of a 2 year-old patient with a long lasting eruption cyst located in the region of tooth 54.